Emerging topics on differential equations and their applications : proceedings on Sino-Japan Conference of Young Mathematicians on emerging topics on differential equations and their applications, Nankai University, China, 5-9 December 2011 - Chen, Hua; Long, Yiming; Nishiura, Yasumasa, 1950- (Nankai series in pure, applied mathematics and theoretical physics ;, 2013)
The aim of the Sino-Japan Conference of Young Mathematicians was to provide a forum for presenting and discussing recent trends and developments in differential equations and their applications, as well as to promote scientific exchanges and collaborations among young mathematicians both from China and Japan. The topics discussed in the proceedings include mean curvature flows, KAM theory, N-body problems, flows on Riemannian manifolds, hyperbolic systems, vortices, water waves, and reaction diffusion systems.